NILAI-NILAI DALAM NOVEL PARTIKEL KARYA DEWI LESTARI (DEE) - (F11409037), Nurlinda; ., H. Martono; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The research is motivated by the desire of researchers to understand more about the novel Particle, not only about the story but about the messages to be conveyed to the reader the author. The method used in this research is descriptive qualitative research forms. The approach used in this study is a dynamic structural approach. Data collection in this study was done as carefully classify and describe, as precisely and deeply as possible elements of literature of the subject of study that emphasizes the values ??that exist in the novel particle. Sources of data in this study is novel Particle DEE work study while data is sentences, phrases and words that contain the value of education, religious values??, social values??, and the value of the individual. The technique used in this study is a documentary study technique. Based on the data analysis it can be concluded that the values ??in the novel Particle DEE work consists of the value of education, religious values??, social values??, individual values??. Keywords: Values, Novel, and Particle Abstrak: Penelitian ini dilatarbelakangi oleh keinginan peneliti untuk lebih memahami novel Partikel, bukan hanya mengenai ceritanya melainkan mengenai pesan yang ingin disampaikan pengarang kepada pembacanya. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan bentuk kualitatif. Pendekatan yang digunakan dalam penelitian ini yaitu pendekatan strukturalisme dinamis. Pengumpulan data dilakukan dengan mengklasifikasikan dan mendeskripsikan unsur karya sastra yang menjadi pokok telaah yang menekankan pada nilai-nilai yang ada dalam novel Partikel. Sumber data adalah novel Partikel karya DEE sedangkan data penelitian adalah kalimat, frasa, dan kata yang mengandung nilai pendidikan, religius, sosial, dan nilai individu. Teknik yang digunakan adalah teknik studi dokumenter. Berdasarkan analisis data dapat disimpulkan bahwa nilai-nilai dalam novel Partikel karya DEE terdiri dari nilai pendidikan, religius, sosial, individu. Kata Kunci: Nilai-Nilai, Novel, dan Partikel